2013
DOI: 10.7120/09627286.22.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Using multiple joystick systems in computerised enrichment for captive orangutans

Abstract: It has been suggested that providing multiple computers with automatic reward dispensers as enrichment to captive orangutans (Pongo spp) (as opposed to a single computer, with a care-staff person delivering reinforcers) might help improve behavioural outcomes. The purpose of the current study was to test this hypothesis by providing two computers with automatic reward dispensers to eight orangutans housed in four male-female pairs at Zoo Atlanta, USA. Subjects were observed for ten days during each of three ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
3
11
0
Order By: Relevance
“…This approach can have safety risks and may be prone to unintended researcher‐bias effects. Alternatively, such reinforcement can be distributed via an automatic feeder integrated with the software system (e.g., Mallavarapu, Bloomsmith, Kuhar, & Maple, ). Such systems are more experimentally reliable, but proper upkeep of the systems is required to prevent feeder malfunctions that may disrupt the reinforcement schedule.…”
Section: Logistical Considerations Of Zoo‐based Touchscreen Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach can have safety risks and may be prone to unintended researcher‐bias effects. Alternatively, such reinforcement can be distributed via an automatic feeder integrated with the software system (e.g., Mallavarapu, Bloomsmith, Kuhar, & Maple, ). Such systems are more experimentally reliable, but proper upkeep of the systems is required to prevent feeder malfunctions that may disrupt the reinforcement schedule.…”
Section: Logistical Considerations Of Zoo‐based Touchscreen Researchmentioning
confidence: 99%
“…More recently, touchscreen systems have been shown to provide enriching effects for a range of primate and carnivore species in zoo settings (Boostrom, ; Mallavarapu et al, ; Perdue, ; Tarou et al, ). For instance, during the introduction of a cognitive research program at Scotland's Edinburgh Zoo, researchers observed that although chimpanzees did not understand the cognitive task presented to them, their repeated use of the touchscreen showed that they found it reinforcing (Herrelko, Vick, & Buchanan‐Smith, ).…”
Section: The Implications Of Zoo‐based Touchscreen Research For Animamentioning
confidence: 99%
“…However, at the same zoo, increased aggression was observed in the presence of a computer‐joystick CT system provided to orangutan dyads off exhibit (Tarou, Kuhar, Adcock, Bloomsmith, & Maple, ). A follow‐up study to Tarou et al () reported no increase in agonistic behavior when a CT device was present; however, the presence of a second testing apparatus decreased affiliative behavior between orangutans compared to when only one testing apparatus was available (Mallavarapu, Bloomsmith, Kuhar, & Maple, ).…”
Section: Statement Of Problemmentioning
confidence: 94%
“…Three of them (Satu, Madu, and Chantek) had been tested in Salwiczek et al (2012)'s original plate study and had failed. All subjects were also tested in an unrelated computerized‐touchscreen task during the period of our study, and some had participated in other computerized tasks (Diamond et al, 2016; Mallavarapu et al, 2013; Paxton Gazes et al, 2017) and manual cognitive tests (Anderson et al, 2007; Brosnan, Flemming, et al, 2011; Flemming et al, 2012; Mallavarapu, 2009; Talbot et al, 2015) prior this one. One female, Madu, was reared in a computer‐enriched environment at the Georgia State University Language Research Center, where she participated in various cognitive tests (Beran, 2002; Washburn et al, 2007).…”
Section: Methodsmentioning
confidence: 99%